Cytotoxic activity of proteins isolated from extracts of Corydalis cava tubers in human cervical carcinoma HeLa cells - Balcerkiewicz Stanislaw; Wyrzykowska Danuta; Bialas Wojciech; Wolun-Cholewa Maria; Nawrot Robert; Gozdzicka-Jozefiak Anna (BMC, 2010)
Abstract Background Corydalis cava Schweigg. & Koerte, the plant of numerous pharmacological activities, together with the studied earlier by our group Chelidonium majus L. (Greater Celandine), belong to the family Papaveraceae. The plant grows in Central and South Europe and produces the sizeable subterraneous tubers, empty inside, which are extremely resistant to various pathogen attacks. The Corydalis sp. tubers are a rich source of many biologically active substances, with the extensive use in European and Asian folk medicine. They have analgetic, sedating, narcotic, anti-inflammatory, anti-allergic and anti-tumour activities. On the other hand, there is no information about possible biological activities of proteins contained in Corydalis cava tubers. Methods Nucleolytic proteins were isolated from the tubers of C. cava by separation on a heparin column and tested for DNase activity. Protein fractions showing nucleolytic activity were tested for cytotoxic activity in human cervical carcinoma HeLa cells. Cultures of HeLa cells were conducted in the presence of three protein concentrations: 42, 83 and 167 ng/ml during 48 h. Viability of cell cultures was appraised using XTT colorimetric test. Protein fractions were separated and protein bands were excised and sent for identification by mass spectrometry (LC-ESI-MS/MS). Results The studied protein fractions showed an inhibiting effect on mitochondrial activity of HeLa cells, depending on the administered dose of proteins. The most pronounced effect was obtained with the highest concentration of the protein (167 ng/ml) - 43.45 ± 3% mitochondrial activity of HeLa cells were inhibited. Mass spectrometry results for the proteins of applied fractions showed that they contained plant defense- and pathogenesis-related (PR) proteins. Conclusions The cytotoxic effect of studied proteins toward HeLa cell line cells has been evident and dependent on increasing dose of the protein. The present study, most probably, represents the first investigations on the effect of purified PR proteins from tuber extracts of a pharmacologically active plant on cell lines.